2018
DOI: 10.1177/2380084418774549
|View full text |Cite
|
Sign up to set email alerts
|

Child and Parent Demographic Characteristics and Oral Health Perceptions Associated with Clinically Measured Oral Health

Abstract: Objective: To examine child and parent reports about the child's oral health and assess the associations of these reports with clinical assessments of oral health status by dental examiners. Methods: Surveys with 139 items for children and 133 items for parents were administered by Audio Computer-Assisted Self-Interview Software. In addition, the Children's Oral Health Status Index (COHSI) was computed from a dental examination. Results: A total of 334 families with children ages 8 to 17 y participated at 12 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…In this study, we used RF to identify questionnaire items that were predictors of active caries and caries experiences using the DMFT index among 2 to 7-year-old children. This is the most recent of multiple papers that develop oral health algorithms or tools which could be used by dentists, oral health researchers and professionals and public policy makers for oral health screening, program assessment, oral health evaluation and oral health management and policy planning [14][15][16][17][18]26]. The studies in this series on children between 8 and 17 years of age (where both parents and children completed the questionnaire) [14][15][16][17][18] showed similar predictors of oral health as we found in our study among children between 2 and 7 years of age (where only the parents completed the questionnaire).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used RF to identify questionnaire items that were predictors of active caries and caries experiences using the DMFT index among 2 to 7-year-old children. This is the most recent of multiple papers that develop oral health algorithms or tools which could be used by dentists, oral health researchers and professionals and public policy makers for oral health screening, program assessment, oral health evaluation and oral health management and policy planning [14][15][16][17][18]26]. The studies in this series on children between 8 and 17 years of age (where both parents and children completed the questionnaire) [14][15][16][17][18] showed similar predictors of oral health as we found in our study among children between 2 and 7 years of age (where only the parents completed the questionnaire).…”
Section: Discussionmentioning
confidence: 99%
“…Parents from disadvantaged groups were more likely to rate their children's oral health less favorably. Another study found poorer oral health ratings from single and migrant parents (Marcus et al 2018). An association between household income and parental ratings was supported by some studies (Talekar et al 2005;Piovesan et al 2011) but not all (Sohn et al 2008;Gomes et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Parental ratings often also differ from child self-ratings. As a proxy for child self-ratings, parental ratings are more valid for observable factors, such as eating and speaking, and less valid for subjective factors, such as aesthetics and pain (Reissmann et al 2017;Marcus et al 2018). However, despite limitations inherent in proxy assessments, parental ratings provide an insight into parents' understanding of oral health and disease and their priorities and concerns (Locker and Miller 1994)-information complementary to that obtained from clinical examinations.…”
Section: Introductionmentioning
confidence: 99%
“…While 90% of children reported speaking English at home, 33% of parents responded that English was not their primary language. Almost three‐quarters of parents were female as were those either married or living with a partner; also, three‐quarters of the households had one or more fully employed members, while 11% of households …”
Section: Methodsmentioning
confidence: 99%